Study of the upper epidermis of leaves of Zizyphus species and varieties in Central and Southern Iraq - Kamil, I J; Al-hassnawy, S H H (Plant Science Today, 2025)
The results showed that some anatomical features of the leaves have good taxonomic value for distinguishing between these species and varieties. The upper epidermal cells of the studied species and varieties showed clear differences in their dimensions. Although the two species Z. mauritiana and Z. spina-christi, existed under the same environmental conditions, the dimensions of the upper epidermal cells of the first species were more significant than those of the second, which made them a distinctive feature of this species. Z. nummularia, the upper epidermis of the varieties of this species, was also significant in dimensions, unlike Z. nummularia, in which the upper epidermal cells were large in dimensions. The difference was also evident in the thickness of the surface walls of the upper epidermal cells, which were thicker in most species of Z. mauritiana than in the rest of the species, especially the cells of Armouti Tailandy, which were even thicker than the walls of the upper epidermal cells of Z. nummularia, despite the harsh conditions in which this species lives. The variation in the distribution of stomata on the surface of the upper epidermis was apparent between species and sometimes between varieties of the same species. As mentioned in the results, this variation helped include the species and varieties in one group. This reflects the close evolutionary relationship between them. Then, the frequency of stomata on the surface of the upper epidermis of species Z. nummularia is higher than that of the rest of the species. This may seem natural for the species Z. nummularia due to the nature of the desert environment.